The study of disproportionately low numbers of Hispanic community college presidents in the United States - Villarreal, Natalie Chapa (Kansas State University, 2020)
The purpose of this study was to understand the disproportionately low numbers of Hispanic community college leaders in the president/CEO position. With half of the Hispanic population enrolling in community colleges, it is imperative to address the low numbers of Hispanic presidents leading those institutions. Studies from the past 30 years have established priorities to support minority students in post-secondary education. Hispanics students report having minority leadership on campus helps to create a supportive environment which helps a student feel connected and to thrive academically. This study employed a grounded theory approach to understand and analyze the lived experiences of Hispanic executive leaders employed at a two-year higher education institution. The researcher using a qualitative search design focused on understanding the challenges and opportunities Hispanics face when aspiring to become a community college president. Fifteen Hispanic community college leaders were drawn from a purposive sampling, which included community college senior leadership across the United States. Interviews were conducted in a semi-structured, open-ended interview protocol. By using this fluid structure, it allowed the researcher to collect data that gave insight to Hispanic leaders in the community college world. The research questions that guided this study included: 1) What are the experiences that Hispanic leaders face on the pathway to the presidency? 2) What are the cultural practices/norms that impact Hispanics in their quest for the community college presidency? 3) What has been the contribution of the Hispanic network in preparing for the presidency? The following themes emerged from the findings: support and mentorship, leadership programs, lack of mobility and time commitment, positive attributes of the Hispanic culture, and the pipeline of Hispanic leaders who are ready to lead. This group of leaders have faced many of the same challenges that their predecessors faced over 30 years ago; however, the findings show that 70% of the participants in this study are ready to take on the path to the presidency. Critical strategies divided into four notable areas for the advancement of Hispanic leaders include: being prepared, establishing relationships, being intentional and taking responsibility. Intentional hiring practices of two year institutions; the need to attend leadership programs to gain social capital and mentorship; preparing oneself with a doctoral degree; learning one’s craft; taking responsibility for self and other Hispanic leaders to build and strengthen the pipeline were mentioned as important components of the strategies. Recommendations for future development of Hispanic leaders include creating new programs and increasing current programs that support the advancement of Hispanic leaders in higher education; and, creating stronger mentorship programs for individuals interested in executive leadership early on in their careers.
Keywords: Community College; Hispanic President; Leadership Strategies